2017
DOI: 10.4314/jab.v109i1.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact de l’emballage et de la durée de conservation sur la qualité nutritionnelle et microbiologique des biscuits de sorgho enrichis au moringa et à la spiruline

Abstract: Songré-Ouattara et al ., J. Appl. Biosci. 2017 Impact de l'emballage et de la durée de conservation sur la qualité nutritionnelle et microbiologique des biscuits de sorgho enrichis au moringa et à la spiruline

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
4
6
0
Order By: Relevance
“…The ash content of the cookies was around 2%. This value is similar to the results of Songré-Ouattara et al [8,9]. These authors have reported ash content going of 2% to 4% on sorghum cookies produced with a margarine.…”
Section: Physicochemical Composition Of the Cookiessupporting
confidence: 91%
See 4 more Smart Citations
“…The ash content of the cookies was around 2%. This value is similar to the results of Songré-Ouattara et al [8,9]. These authors have reported ash content going of 2% to 4% on sorghum cookies produced with a margarine.…”
Section: Physicochemical Composition Of the Cookiessupporting
confidence: 91%
“…Nevertheless, the pH value found in this study was higher than the pH value reported by Vatankhah The lipid content of the control cookies (M20) and CPO16 was the lowest, 20.82 ± 0.08 and 20.61 ± 0.01% respectively. These values were also similar to that of Songré-Ouattara et al [8,9]. These authors have reported 20.9 ±1,4% as lipid content of their cookies.…”
Section: Physicochemical Composition Of the Cookiessupporting
confidence: 90%
See 3 more Smart Citations